Reciprocity and governmentality after introducing religious presence in medium and maximum security prisons in the province of Santa Fe - Manchado, Mauricio (Revista de Antropología Social, 2016)
In this work we will research on the reconfiguration of institutional dynamics after the presence of the pentecostal-evangelical religious group inside two prisons in the province of Santa Fe, Argentina. The two cases are: the penitentiaries No. 3 —medium security— and No. 11 —maximum security—. We will discuss the relations of reciprocity resulted by the presence of religious group and how these relationships will define new strategies of government by the prison service as well as how power relations are redesigned inside the prison. A comparative approach is developed to prove the following hypothesis: the presence of evangelical-pentecostal religious group not only constructs a common social system matrix, performance and reciprocity in confinement but also strengthens the way its operates according to a precise identification of subject needs and opportunities as they are being incarcerated or discharged.
Keywords: prisons; evangelical and pentecostal religious groups; reciprocity; power; governmentality.